The catalytic subunit DNA-dependent protein kinase (DNA-PKcs) facilitates recovery from radiation-induced inhibition of DNA replication - Guan, Jun (Oxford University Press, 2000)
Exposure of cells to ionizing radiation inhibits DNA replication in a dose-dependent manner. The dose response is biphasic and the initial steep component reflects inhibition of replicon initiation thought to be mediated by activation of the S-phase checkpoint. In mammalian cells, inhibition of replicon initiation requires the ataxia telagiectasia mutated (ATM) gene, a member of the phosphatidyl inositol kinase-like (PIKL) family of protein kinases. We studied the effect on replicon initiation of another member of the PI-3 family of protein kinases, the catalytic subunit of DNA-dependent protein kinase (DNA-PKcs) by measuring either total DNA synthesis, or size distribution of nascent DNA using alkaline sucrose gradient centrifugation. Exposure of human cells proficient in DNA-PKcs (HeLa or M059-K) to 10 Gy inhibited replicon initiation in a time-dependent manner. Inhibition was at a maximum 1 h after irradiation and recovered at later times. Similar treatment of human cells deficient in DNA-PKcs (M059-J) inhibited replicon initiation to a similar level and with similar kinetics; however, no evidence for recovery, or only limited recovery, was observed for up to 8 h after irradiation. In addition a defect was observed in the maturation of nascent DNA. Similarly, a Chinese hamster cell line deficient in DNA-PKcs (irs-20) showed little evidence for recovery of DNA replication inhibition up to 6 h after irradiation, whereas the parental CHO cells showed significant recovery and an irs-20 derivative expressing the human DNA-PKcs complete recovery within 4 h. Normal kinetics of recovery were observed in xrs-5 cells, deficient in Ku80; in 180BR cells, deficient in DNA ligase IV; as well as XR-1 cells, deficient in XRCC4, an accessory factor of DNA ligase IV. Since all these cell lines share the DNA double strand break rejoining defect of M059-J and irs20 cells, the lack of recovery of DNA replication in the latter cells may not be attributed entirely to the prolonged presence of unrepaired DNA dsb. We propose that DNA-PKcs, in addition to its functions in the rejoining of DNA dsb and in DNA replication, also operates in a pathway that in normal cells facilitates recovery of DNA replication after irradiation.